Feeding and ecomorphology of three clupeoids in the N Aegean Sea - KARACHLE, P. K.; STERGIOU, K. I. (Mediterranean Marine Science, 2013)
The present study examines the feeding habits of anchovy (Engraulis encrasicolus), sardine (Sardina pilchardus) and round sardinella (Sardinella aurita). The results are combined with previously published information on feeding-related morphological features (i.e. mouth area, intestine length and tail area) in order to explore morphological affinities between species and the effect of ecomorphology on their co-existence. These species were mainly zooplanktivorous and no dietary differences were found with sex and season. Anchovy preyed mainly on Crustacea larvae, whereas sardine and round sardinella on Copepoda. In the majority of cases (>90%), the individual fractional trophic level of all species ranged between 3.0 and 3.5, classifying them as omnivores with preference to animals. The feeding-related morphological features differed between anchovy and the two other species, whereas only intestine length differed between sardine and round sardinella. The fact that round sardinella’s diet and morphology show a greater resemblance to those of sardine, further support the hypothesis that is a particulate feeder as sardine. Hence the three species tend to exploit the same food resources differently throughout the year. Thus, they make best use of the environment and its resources, in order to avoid competition and achieve optimum feeding conditions throughout their life cycles